Relationship between measured maximal oxygen uptake and aerobic endurance performance with running repeated sprint ability in young elite soccer players - Aziz, A. R.; Mukherjee, S.; Chia, M. Y. H.; Teh, K. C. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim. The aim of the study was to determine the relationships between maximal oxygen uptake (VO2max) in a maximal treadmill run and the aerobic endurance performance in the 20-m multistage shuttle run (MST) test, with the performance indices obtained in the running repeated sprint ability (rRSA) test, in elite youth soccer players. Methods. Thirty-seven adolescent male outfield players performed on separate days and in random order the treadmill run test and the MST, to obtain their measured VO2max and aerobic endurance performance (via the number of completed shuttles in the MST), respectively. Players also completed the rRSA test of 6¥20-m all-out sprints, interspersed with 20 s of active recovery. Results. There was a significant moderate correlation between measured VO2max (in L/min and mL/kgmin) and MST results (r=0.43 and 0.54, P<0.05, respectively). There was no significant correlation between measured V.O2max and aerobic endurance performance with any of the performance indices in the rRSA test (all P>0.05). Conclusion. The moderate association between the measured VO2max and MST suggests that both tests were plausibly measuring different aspects of a player's aerobic fitness. The lack of association between measured VO2max and aerobic endurance performance in the MST with performance in the rRSA suggests that aerobic fitness per se is poorly associated with performance in the rRSA in elite youth soccer players.